Aluminum in Effluents and Sludges from the Preliminary Coagulation in Dairy Factory Aerated Balancing Tanks: An Analytical and Sorption Study - Michał Sadowski; Piotr Anielak; Wojciech M. Wolf (Journal of Chemistry)
The coagulation process is used as the first step for the chemical treatment of liquid waste. Resulting wet sludge is treated with coagulants or polyelectrolytes to improve dewatering characteristics of its so-called conditioning. The coagulants such as aluminum sulphate or polyaluminum chloride (Al2Cln(OH)6−n) are widely used for dairy wastewater treatment systems. The pretreatment dairy sludge can be applied in agriculture as fertilizer containing valuable nutrients. Hence, a simple, cost effective, and rapid method for the determination of aluminum content in the sludge is essential for calculation of the appropriate coagulant dose at the sludge pretreatment process. In this paper either colorimetric or atomic absorption spectrometric methods as applied for the determination of aluminum concentration in the dairy wastewater are compared. For colorimetric method, the optimum experimental conditions such as pH, reaction time, and concentration of other ions in the sample were determined. The sorption isotherms of aluminum on the activated sludge were determined for diverse aluminum species.